(untitled) (Asian Business Research, 2016)
This paper aims to investigate the impact of subliminal messages through music in Hyper stores in Punjab, Pakistan and their effect on consumer behavior. Researcher used the music to test the participants of this research with three different conditions; to match the suggestions and subliminal message; the use of suggestion as mismatched with subliminal message; No suggestions for subliminal message. The aim of study was to find out the impact of variables (subliminal messages and the effect of age) on consumer behavior. The study explores the methodology with focuses on evidence from previous literature and empirical studies. Researcher will use explanatory approach with quantitative methods (Regression analyses) to collect and analyze the data. Researcher used questionnaire and survey to measure the participants and to know about subliminal messages, and how they believe on subliminal messages. Population of this study was the consumers of Hyper Stores in Punjab, Pakistan. Major limitations of this study were its context, because it only lies between consumers of Hyper Stores. Progress towards this area has been started, and remains it’s a limited factor to describe the findings from this research. In education it’s noted to include the Subliminal Messages, consciously or unconsciously, and may use to hinder the originality of students. To induce this type of messages provides the opportunities of redirecting or moving the design and process towards necessary direction. Public realized about the products which contain this types of messages are likely to impact and public try to manipulate by the claims of advertising. The paper extends the new way of manipulating the consumers and divert their mind to enhance the marketing, and previous reviews by its induction of results from a series of empirical studies that have worked in past.